(untitled) (Baghdad Science Journal, 2021)
The relation between anemia and inflammatory immune response has lately had much attention. This research was conducted from October 2018 until April 2019, including (110) children below 12 years from both gender in some Hospitals, Primary Health care centers, Public Primary Schools and Kindergarten in Baghdad, Iraq. The objective of this study is to determine the possible correlation between iron deficiency anemia and inflammatory immune response among children infected with Entamoeba histolytica or Giardia lamblia. Blood samples were taken from all groups to measure hemoglobin level, serum iron, total iron binding capacity (TIBC), mean corpuscular volume (MCV), and mean corpuscular hemoglobin concentration (MCHC), while the inflammatory related immune response was evaluated by measuring IL-6 and ferritin. Student T-Test was used to compare between means. The results showed that both hemoglobin and iron concentrations were significantly (P) ˂ 0.01 lower in infected children compared with control, as well as both IL-6 and ferritin levels were significant where (P) ˂0.05 amplified among infected children compared to control. Microcytic hypochromic anemia was observed in the majority of infected children, while normocytic normochromic RBCs was recorded in the majority of control children.